The Role of Government in Fostering and Promoting Songkok MSME Products to Go International - Nadliroh, Indah Datin; Sudarmiatin, Sudarmiatin; Handayati, Puji (IJBLE Scientific Publications Community Inc., 2025)
Micro, Small, and Medium Enterprises (MSMEs) are essential to the Indonesian economy. One is Songkok, which has strong cultural values ​​and a strong identity. Despite great growth potential, songkok products still face difficulties entering the international market. Therefore, the government's role is significant in fostering and promoting Songkok MSME products so that they can compete in the global market. Through various policies and support programs such as training, improving product quality and access to international marketing, the government is essential in creating opportunities for developing Songkok MSME actors. Promotion through digital platforms, international exhibitions and cooperation with other countries are strategic steps in introducing Songkok products to the global market. This article discusses the role of the government in supporting Songkok MSME actors so that their products can develop internationally, as well as the challenges and opportunities in the process. With the proper guidance, songkok products have the potential to be widely known and make a significant contribution to the Indonesian economy.